A novel drug–drug coamorphous system without molecular interactions: improve the physicochemical properties of tadalafil and repaglinide. Issue 1 (2nd January 2020) - Su, Meiling; Xia, Yanming; Shen, Yajing; Heng, Weili; Wei, Yuanfeng; Zhang, Linghe; Gao, Yuan; Zhang, Jianjun; Qian, Shuai
Abstract : The coamorphous tadalafil–repaglinide (molar ratio, 1 : 1) prepared by solvent-evaporation method significantly improve the physicochemical properties of tadalafil and repaglinide. Abstract : Tadalafil and repaglinide, categorized as BCS class II drugs, have low oral bioavailabilities due to their poorly aqueous solubilities and dissolutions. The aim of this study was to enhance the dissolution of tadalafil and repaglinide by co-amorphization technology and evaluate the storage and compression stability of such coamorphous system. Based on Flory–Huggins interaction parameter ( χ ≤ 0) and Hansen solubility parameter ( δ t ≤ 7 MPa 0.5 ) calculations, tadalafil and repaglinide was predicted to be well miscible with each other. Coamorphous tadalafil–repaglinide (molar ratio, 1 : 1) was prepared by solvent-evaporation method and characterized with respect to its thermal properties, possible molecular interactions. A single T g (73.1 °C) observed in DSC and disappearance of crystallinity in PXRD indicated the formation of coamorphous system. Principal component analysis of FTIR in combination with Raman spectroscopy and Ss 13 C NMR suggested the absence of intermolecular interactions in coamorphous tadalafil–repaglinide. In comparison to pure crystalline forms and their physical mixtures, both drugs in coamorphous system exhibited significant increases in intrinsic dissolution rate (1.5–3-fold) and could maintain supersaturated level for at least 4 hours in non-sink dissolution. In addition, the coamorphous tadalafil–repaglinide showed improved stability compared to the pure amorphous forms under long-term stability and accelerated storage conditions as well as under high compressing pressure. In conclusion, this study showed that co-amorphization technique is a promising approach for improving the dissolution rate of poorly water-soluble drugs and for stabilizing amorphous drugs.